2021
DOI: 10.3390/su131810001
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Spinach Produced in Central and Southern Italy

Abstract: Environmental sustainability continues to attract global interest, especially due to the issue of climate change. The agri-food sector is considered a major contributor to climate change as processes and activities within the sector can negatively impact the environment. The recent changing dietary pattern towards increased vegetable consumption implies a consequent increase in production to meet demand. This study assessed the environmental performance of 1 kg of spinach/FU (Functional Unit) cultivated by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Boscalid contributes to freshwater ecotoxicity and human toxicity, whereas mancozeb contributes to climate change due to its production stage, and terrestrial acidification. Finally, it should be noted that even though the EU expects an improved environmental performance due to increasing organic production, Pedretti et al [30] reported no statistical difference due to pesticides application between organic and conventional production of spinach leaf.…”
Section: Fungicides Contribution To Environmental Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Boscalid contributes to freshwater ecotoxicity and human toxicity, whereas mancozeb contributes to climate change due to its production stage, and terrestrial acidification. Finally, it should be noted that even though the EU expects an improved environmental performance due to increasing organic production, Pedretti et al [30] reported no statistical difference due to pesticides application between organic and conventional production of spinach leaf.…”
Section: Fungicides Contribution To Environmental Impactsmentioning
confidence: 99%
“…This does not necessarily mean that the quantity of active ingredients (dosage) is smaller in fruits than vegetables, cereals, or rapeseed. In contrast, vegetables employ the largest variety of fungicides, with systemic pesticides dominating, especially azoxystrobin [27][28][29] and boscalid [27,30,31]. For both fruits and vegetables, the most common contact fungicide is mancozeb [8,11,19,28,29,32].…”
Section: Active Ingredientmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, weed control is challenging in spinach fields since very few herbicides are available for use in this crop [17]. During past years, lenacil was the dominant herbicide for selective weed control in several spinach-producing countries in Europe [18][19][20]. However, it is very likely to be withdrawn from the market in European Union (EU) after the end of 2021 due to concerns for its environmental fate and impact on human health and non-target organisms [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Phenmedipham, a photosystem II (PS II) inhibitor, is the only option for the selective control of broadleaf weeds [23,24]. For the selective control of grass weeds, available herbicides are limited to acetyl-CoA-carboxylase (ACCase) inhibitors (i.e., cycloxydim, quizalofopp-ethyl, and propaquizafop) [18,20]. There is much evidence that overreliance on these herbicides will lead to the rapid evolution of herbicide-resistant weed populations [25].…”
Section: Introductionmentioning
confidence: 99%